Mesenchymal Stromal Cell Therapy Is Associated With Increased Adenovirus‐Associated but Not Cytomegalovirus‐Associated Mortality in Children With Severe Acute Graft‐Versus‐Host Disease. (5th June 2014) - Calkoen, Friso G.J.; Vervat, Carly; van Halteren, Astrid G.S.; Welters, Marij J.P.; Veltrop-Duits, Louise A.; Lankester, Arjan C.; Egeler, R. Maarten; Ball, Lynne M.; van Tol, Maarten J.D.
Abstract : This study shows an association between human adenovirus (HAdV) infections occurring after mesenchymal stromal cell (MSC) infusion and decreased survival in patients treated for severe steroid‐refractory acute graft‐versus‐host disease. In vitro data demonstrate a suppressive effect of MSCs on proliferation and activation of HAdV‐specific T cells, but results do not support a negative impact on antiviral T‐cell‐driven immune responses in vivo; however, the benefits with MSCs seem to outweigh the potentially increased risk of infections. Abstract : Beneficial effects of mesenchymal stromal cells (MSCs) in patients with severe steroid‐refractory acute graft‐versus‐host disease (aGvHD) have been reported. However, controversy exists about the effect of MSCs on virus‐specific T cells. We evaluated 56 patients with grade II‐IV aGvHD who responded to steroids ( n = 21) or were steroid refractory receiving either MSCs ( n = 22) or other second‐line therapy ( n = 13). Although the overall incidence of cytomegalovirus (CMV), Epstein‐Barr virus, and human adenovirus (HAdV) infections was not significantly increased, HAdV infection was associated with decreased survival in children treated with MSCs. Thus, we investigated in vitro the effects of MSCs on virus‐specific T cells. Both CMV‐specific and, to a lesser extent, HAdV‐specific T‐cell activation and proliferation were negatively affected by MSCs either after induction of a response in peripheral blood mononuclear cells (PBMCs) or after restimulation of virus‐specific T‐cell lines. In patient‐derived PBMCs, CMV‐specific proliferative responses were greatly decreased on first‐line treatment of aGvHD with systemic steroids and slowly recovered after MSC administration and tapering of steroids. HAdV‐specific T‐cell proliferation could not be detected. In contrast, the proportion of CMV‐ and HAdV‐specific effector T cells, measured as interferon‐γ‐secreting cells, remained stable or increased after treatment with MSCs. In conclusion, although in vitro experimental conditions indicated a negative impact of MSCs on CMV‐ and HAdV‐specific T‐cell responses, no solid evidence was obtained to support such an effect of MSCs on T‐cell responses in vivo. Still, the susceptibility of steroid‐refractory severe aGvHD patients to viral reactivation warrants critical viral monitoring during randomized controlled trials on second‐line treatment including MSCs.